CO2 derived amino-alcohol compounds for preparation of polyurethane adhesives. (May 2019) - Li, Xiaoyun; Ke, Jiexi; Wang, Junwei; Kang, Maoqing; Zhao, Yuhua; Li, Qifeng; Liang, Chen
Graphical abstract: Highlights: A series of CO2 derived amino-alcohol compounds were synthesized. Structures of amino-alcohol compounds influenced the properties of adhesives. PU adhesives from the synthesized amino-alcohol compounds showed excellent adhesion properties. CO2 derived adhesives showed other considerable properties. Abstract: A series of novel amino-alcohol curing agents for PU adhesives were synthesized from CO2, glycidyl ether and diamine through carbonation and amination reactions. By physically evaluating the compounds through FT-IR and 1 H NMR spectroscopy and mechanically analyzing the adhesives through T-peel strength tests, the raw materials have successfully been transformed into curing agents and the curing agents were found to endow the adhesives with specific structures and unique properties. For PVC bonding, compared to the traditional curing agents HDA and HDO, the T-peel strength and medium resistance from the novel amino-alcohol compounds improved. Further analysis revealed distinction in mechanical properties for different curing agents, the trifunctional curing agent exhibited the largest tensile strength and hardness. Moreover, thermal analysis of the adhesives demonstrated the considerable thermal stability to those prepared from HDA and HDO.